Pengaruh Pemberian Pinjaman Modal Usaha Terhadap Peningkatan Pendapatan Pelaku Usaha (Studi Kasus Pada Usaha Perdagangan Di Desa Tameran) - Irawan Fakhrudin Mahalizikri; Herbi Herbi (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2021)
This research was carried out on tameran village trading business titled "Effect of Business Capital Lending on Increasing Income of Business Estimation"(Case Study on Trading Business in Tameran Village). In the preparation of this Thesis, the author only restricts to businesses that need funds or venture capital in 2018-2020.Â  Capital borrowers aim to provide additional business capital in Tameran village. In this arrangement, to be able to find out the results of this study the author uses a quantitative methodology to determine the results between the two variables. Data collection was carried out by giving questionnaires totaling 76 respondents, which were distributed to business actors who borrowed funds. Based on the coefficient of determination test with the R Square value of SPSS Version 23, which is equal to 0.898, this figure is also called the coefficient of determination. The magnitude of the number 0.898 is the same as 89.8%. This means that 89.8% of the business capital variable affects the business income variable. While the rest (100% -89.8%), namely 10.2% of business capital, is influenced by other variables that are not included in this research model. Meanwhile, for T count> T Table, which is 25,527> 1.99, it means that H0 is rejected and Ha is accepted.